2020
DOI: 10.1002/jcop.22455
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous and non‐Indigenous parents separated from their children and experiencing homelessness and mental illness in Canada

Abstract: The purpose of this study is to examine the parent-child experiences of Indigenous and non-Indigenous mothers and fathers experiencing homelessness, mental illness, and separation from their children. A qualitative thematic analysis of baseline and 18-month follow-up narrative interviews was used to compare 12 mothers (n = 8 Indigenous and n = 4 nonindigenous) with 24 fathers (n = 13 Indigenous and n = 11 non-Indigenous). First, it was found that children are more central in the lives of mothers than fathers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A study summarizing the experiences of individuals experiencing houselessness also found that Indigenous participants described narrative identities filled with stories of racism, historical trauma, and disconnection from one's culture(s), while those of non-Indigenous participants (specified in this study as White Canadian or European) (66) did not. These results indicated again that access to housing alone may not be enough to see similar improvements in mental health outcomes across populations-access to methods of cultural healing and reclamation will be required as well (66). Finally, one study found that gaps in suicide-related behaviors between Indigenous populations living off-reserve and non-Indigenous populations in Canada were largely due to differences in the effects of unobserved determinants (i.e., not socioeconomic factors such as income and employment which had been included in the analytical model) (67).…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…A study summarizing the experiences of individuals experiencing houselessness also found that Indigenous participants described narrative identities filled with stories of racism, historical trauma, and disconnection from one's culture(s), while those of non-Indigenous participants (specified in this study as White Canadian or European) (66) did not. These results indicated again that access to housing alone may not be enough to see similar improvements in mental health outcomes across populations-access to methods of cultural healing and reclamation will be required as well (66). Finally, one study found that gaps in suicide-related behaviors between Indigenous populations living off-reserve and non-Indigenous populations in Canada were largely due to differences in the effects of unobserved determinants (i.e., not socioeconomic factors such as income and employment which had been included in the analytical model) (67).…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…Despite the centrality of children in Indigenous families and communities, and the alarming overrepresentation of Indigenous family separation due to systemic violence, we know little about the parent-child outcomes of housing and service interventions with Indigenous parents who have been separated from their children and experiencing homelessness in Canada. A recent HF study (Caplan et al, 2020) with Indigenous and non-Indigenous parents who had been separated from their children and experiencing homelessness and mental illness in Canada showed that:…”
Section: Indigenous Families Centrality Of Children and Cultural Adap...mentioning
confidence: 99%
“…Despite the centrality of children in Indigenous families and communities, and the alarming overrepresentation of Indigenous family separation due to systemic violence, we know little about the parent–child outcomes of housing and service interventions with Indigenous parents who have been separated from their children and experiencing homelessness in Canada. A recent HF study (Caplan et al, 2020) with Indigenous and non-Indigenous parents who had been separated from their children and experiencing homelessness and mental illness in Canada showed that:Despite the systematic program to disconnect Indigenous peoples of Turtle Island from their relationships and land—and in spite of experiencing pervasive interpersonal violence and racism—relationships, family support, and cultural healing were central to the recovery and healing experiences of Indigenous parents. Indigenous parents described engaging in cultural practices of traditional healing circles and ceremony, sweats, and powwows; culturally relevant programs; relationships with elders, cultural healers, family, community, and language; (re)connections with nature, animals, and land; (re)connections with parenting knowledge; and holistic worldviews of wellness that balance mental, physical, spiritual, and emotional well-being (Hartmann & Gone, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The low engagement of resources and high prevalence of mental health and substance use problems in these minority communities results in Indigenous parents often also being affected by addiction, mental illness, homelessness, interpersonal and systemic violence, racism and trauma, and separation from their children (Caplan et al, 2020). This in turn can contribute to ambivalent or insecure attachment with their children (Howard et al, 2011;Feizi et al, 2019), which has been linked to anxiety and depressive disorders in adolescence (Lee et al, 2009).…”
Section: Social Factorsmentioning
confidence: 99%